Avaliação do efeito cardioprotetor do nerol em modelo de hipertrofia cardíaca induzida por isoproterenol - Santos, Vinícius Cisneiros de Oliveira (2019)
The nerol is a monoterpene present in several plants such as Cymbopogon flexuosos (lemon grass), Wisteria brachybotrys (wisteria) and Rosa damascaena (rose tea) with antioxidant, anti-inflammatory, antibacterial, antifungal and antiarrhythmic effects. The objective of the present study was to investigate the cardioprotective activity of the nerol on isoproterenol-induced cardiac hypertrophy (ISO) model. Wistar rats (200-250 g, CEPA: 29/18) were distributed in 5 groups and treated for 7 days ip: 1) Control group (CTR; n = 6), animals receiving saline + DMSO 0 ,1%; 2) Nerol group (n = 6), animals treated with 50 mg / kg nerol + 0.1% DMSO; 3) Group hypertrophy (ISO, n = 6), animals receiving ISO (4.5 mg / kg), 4) Group hypertrophy + nerol (ISO + nerol, n = 6), animals received ISO + nerol, Group hypertrophy + N-acetylcysteine (ISO + NAC, n = 6), animals treated with ISO + NAC (50 mg / kg). The morphometric results showed an increase in the heart weight / body weight ratio (4.89 ± 0.13 mg / g) and heart weight / tibia size (350 ± 8.64 mg / cm) in the ISO group, which were in the ISO + nerol group (3.77 ± 0.16 mg / cm and 211.6 ± 3.29 mg / cm, respectively, p <0.05). Enzyme markers were elevated in hypertrophic animals (LDH: 126.8 ± 11.23 U / L, CPK: 235.6 ± 29.9 U / L and CPK-MB 49.5 ± 5.5 U / L ). However, treatment with the nerol was able to prevent these changes (LDH: 78.5 ± 11.29 U / L, CPK: 48.2 ± 9.7 U / L, CPK-MB: 12.9 ± 2, 5 U / L, p <0.05). The treatment with the nerol was able to reduce the duration of the QRS (43.46 ± 0.63 ms to 23.04 ± 0.6 ms, p <0.05) and abolish the T wave inversion characteristic of cardiac hypertrophy and of QTc (from 114.2 ± 0.2 ms to 56.6 ± 5.7 ms, p <0.05). An improvement in ventricular contractility (47.2 ± 3.0 mmHg, p <0.05) was also observed in relation to the hypertrophy group (12.36 ± 4.42 mmHg). No alteration of PRi and heart rate was observed in the experimental groups evaluated. At coronary pressure, we observed a reduction in the hypertrophy group (44.6 ± 1.6 cmH2O, p <0.05) in relation to the control group (90.6 ± 1.7 cmH2O, p <0.05) which was attenuated in the ISO + nerol group (77.6 ± 1.4 cmH2O, p <0.05). The NAC, used as a positive control, was also able to attenuate the morphometric, enzymatic, electrocardiographic and contractile alterations observed in hypertrophic animals. In addition, histopathology (Mansson's Tricycle) revealed significant improvement of tissue fibrosis, inflammatory infiltrate and edema of hypertrophic hearts with nerol treatment. The area of fibrosis and the left ventricular cross-sectional area were reduced by 58% and 36% (n = 6), respectively, in the hypertrophic hearts treated with the nerol. We conclude that the nerol has a cardioprotective effect in a model of isoproterenol-induced cardiac hypertrophy.